FUNGSI DAN MAKNA PERTUNJUKAN TARI SINTRÃˆN DI KABUPATEN PEKALONGAN JAWA TENGAH - Hadi Subagyo (Greget, 2015)
The Sintren dance is a form of folk dance that can be found on the north coast of CentralJava. It is performed by an unmarried female dancer who is in a trancelike state after being possessed by a spirit. It is a highly unique form of performance which has a complex meaning andfunction but its existence is currently a cause for concern since only a small number of groupscontinue to perform this art today. In Pekalongan in particular, the art of Sintren continues to bemulti-functional, and in addition to being a form of entertainment and used for social purposes,it is also closely associated with a ritual function. The meaning contained in the art of Sintrenprimarily describes the life journey of a person from the time he is still inside his motherâ€™s wombto his birth, growth and development, and ultimately his death. The other meaning contained inthe art of Sintren is the poetry which accompanies the performance, describing the beauty of thenatural surroundings, animal and plant life, and things associated with spirits, angels, and goddesses. The poetry is largely in the form of advice or guidance which is reflected in the form offigures of speech.Keywords:Sintren Dance, function, and meaning.